STATUS BEBERAPA SIFAT KIMIA TANAH PADA BERBAGAIPENGGUNAAN LAHAN DI DAS POBOYA KECAMATAN PALU SELATAN - Bakri, Ilham; Thaha, Abdul Rahim; Isrun, Isrun (AGROTEKBIS, 2016)
This research aims is to determine some soil chemical properties on a variety land use in Poboya watershed. While the usefulness of this study are as material information about characteristics of the chemical properties of the various land use in the Poboya watershed which is expected to serve as a reference in treatment planning watershed and soil and water conservation. The method used in this research is using survey methods. Observations and soil sampling done by tactical. The distance between the observation point with other observations point adjusted to the conditions of the survey area. The soil samples were taken from four kinds of state forest land the land cover, shrubs, garden mix and moor. Each type of land use types 5 sub samples were taken and composited, in order to obtain four composite soil samples for laboratory analysis. The analysis includes a soil chemical properties of soil pH, organic C, N - total, P - total, P - available, Potassium, Cation Exchange Capacity and Texture. Results of chemical analysis of several types of land use, forest land has chemical properties that best compared with the chemical properties of the type of land use shrubs, garden mix and moor. Chemical properties on the type of land use mixed gardens and fields are generally relatively low.Â Key Words: Chemical soil, land use type, watershed.